What constitutes evidence of poor prison conditions after Aranyosi and Căldăraru? Examining the role of inspection and monitoring bodies in European Arrest Warrant decision-making. Issue 3 (September 2019) - Rogan, Mary
The case of Aranyosi and Căldăraru confirms that where prison conditions are so poor as to breach fundamental rights, the non-execution of an European Arrest Warrant is justified. Given the high stakes nature of such a decision, this article examines a critical question: What will be the possible sources of evidence which can and should be used in such an assessment? The article posits that prison inspection and monitoring bodies, which have the task of visiting prisons and reporting on them, with a view to the prevention of ill treatment, will take on an important role in this decision-making process. The article examines what this role might entail and the implications of the decision for prison inspection and monitoring bodies.